Analysis Of Accounting Information Systems For Cash Receipts And Disbursements At Family 24 Pagar Dewa Pharmacy, Bengkulu City - Sai, Tunggalan; Wagini, Wagini; Hidayah, Nenden Restu (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2024)
The aim of this research is to analyze the accounting information system for cash receipts and disbursements at the Family 24 Pagar Dewa Pharmacy in Bengkulu City according to Mulyadi's theory (2019:379). The data analysis method is comparative descriptive analysis between the SIA theory of cash receipts and cash disbursements according to Mulyadi and the Family 24 Pagar Dewa Pharmacy, Bengkulu City. The results of the research show that the accounting information system for cash receipts and cash disbursements at the Family 24 Pagar Dewa Pharmacy, Bengkulu City includes: related functions, documents used, accounting records used and procedures that form the system. The cash receipt accounting information system at the Family 24 Pagar Dewa Pharmacy, Bengkulu City has a compatibility with the related functions and the network of procedures that form the system with the theory presented by Mulyadi, because at the Family 24 Pagar Dewa Pharmacy, Bengkulu City there is a cash receipt process and also functions related to receipts. cash but there is no delivery function. For the documents used, there are several documents that are not used by pharmacies because all transactions are carried out computerized. Likewise with recording, only making entries in the cash entry book. The accounting information system for cash disbursements at the Family 24 Pagar Dewa Pharmacy, Bengkulu City, there are conformities and discrepancies between Mulyadi's theory and what is carried out by the Family 24 Pagar Dewa Pharmacy, Bengkulu City. Conformity can be seen from the existing functions which are in accordance with Mulyadi's theory but there is no internal inspection function. The documents used are not in accordance with Mulyadi's theory because many documents are not made by pharmacies, such as requests for making checks and there is also no preparation of funds for disbursement of all cash disbursement transactions directly issued by the cashier or by the pharmacist and disbursement by transfer is carried out by the pharmacy owner